2010
DOI: 10.1002/aoc.1605
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide‐based magnetic nanostructures bearing cytotoxic organosilicon molecules for drug delivery and therapy

Abstract: The results of our own investigation on synthesis, physico-chemical and biological study of iron oxide based magnetic nanoparticles bearing cytotoxic organosilicon molecules of choline and colamine analogues, as potential agents for antitumor therapy, are summarized. These molecules contain hydrophilic head and long lipophilic tails, which are able to deepen inside the first surfactant shell (oleic acid), forming bilayer membrane like structures. Such compositions have a great privilege possessing magnetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recently model magnetic nanoparticles with immobilized cytotoxic organosilicon choline and colamine derivatives have been synthesized, and water‐based magnetic fluids containing model cytotoxic magnetosomes with amphiphilic trialkylsiloxyalkylamines have been obtained according to the developed original approach. It has been demonstrated that resulting magnetic fluids revealed magnetic properties and affected tumour cell lines . The positive results obtained make it possible to expand the research, involving more complex biologically active molecules using the same principal methodology.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently model magnetic nanoparticles with immobilized cytotoxic organosilicon choline and colamine derivatives have been synthesized, and water‐based magnetic fluids containing model cytotoxic magnetosomes with amphiphilic trialkylsiloxyalkylamines have been obtained according to the developed original approach. It has been demonstrated that resulting magnetic fluids revealed magnetic properties and affected tumour cell lines . The positive results obtained make it possible to expand the research, involving more complex biologically active molecules using the same principal methodology.…”
Section: Introductionmentioning
confidence: 93%
“…It has been demonstrated that resulting magnetic fluids revealed magnetic properties and affected tumour cell lines. [20] The positive results obtained make it possible to expand the research, involving more complex biologically active molecules using the same principal methodology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research the procedure for the synthesis of model magnetic NPs with immobilized cytotoxic organosilicon choline and colamine derivatives, accepted as silyl pro‐drugs, has been developed and their water‐based magnetic fluids (MFs) have been prepared . It has been demonstrated that the resulting MFs had magnetic properties and affected tumour cell lines . The positive results obtained stimulated us to extend the research to more complex biologically active structures and to other types of biological activity.…”
Section: Introductionmentioning
confidence: 99%